Managing Classical Islamic Text Literacy Acceleration through Triple Supervisor Small Group Model in Pesantren - Zainal Abidin; Ahmad Qusairi; Ikmal Wahyudi (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2026)
The decline in yellow-book literacy skills at the elementary level is a serious challenge for Islamic boarding schools. This study aims to analyze the strategy of organizing intensive learning to reduce the number of novice students reading the book at the Darullughah Wadda'wah Islamic Boarding School. Using a descriptive qualitative approach, this study examines the Ta'lim al-Muta'allim book guidance program in seven classes of fourth-grade elementary school students. Data were collected through participant observation, in-depth interviews with the Department of Education, and a documentary study of evaluation results. The research findings indicate that the